Neutrino-induced reactions in core-collapse supernovae: Effects on the electron fraction - Saez, M. M. (2018)
Neutrino-induced reactions are a basic ingredient in astrophysical processes like star evolution. The existence of neutrino oscillations affects the rate of nuclear electroweak decays which participates in the chain of events that determines the fate of the star. Among the processes of interest, the production of heavy elements in core-collapse supernovae is strongly dependent upon neutrino properties, like the mixing between different species of neutrinos. In this work, we study the effects of neutrino oscillations upon the electron fraction as a function of the neutrino mixing parameters, for two schemes: the 1+1-scheme (one active neutrino and one sterile neutrino) and the 2+1-scheme (two active neutrinos and one sterile neutrino). We have performed this analysis considering a core-collapse supernovae and determined the physical conditions needed to activate the nuclear reaction chains involved in the r-process. We found that the interactions of the neutrinos with matter and among themselves and the initial amount of sterile neutrinos in the neutrino-sphere might change the electron fraction, therefore affecting the onset of the r-process. We have set constrains on the active-sterile neutrino mixing parameters. They are the square-mass-difference ∆m^2_14 , the mixing angle sin^2(2θ_14), and the hindrance factor Xi_s for the occupation of sterile neutrinos. The calculations have been performed for different values of X_alpha, which is the fraction of alpha particles. For X_alpha=0 the r-process is taking place if ∆m^2_14 ≥ 2 eV^2 , sin^2(2θ_14) < 0.8 and Xi_s < 0.5. For larger values of X_alpha the region of parameters is strongly reduced. The present results are compared to results available in the literature.